Hepatic safety and lack of antiretroviral interactions with buprenorphine/naloxone in HIV-infected opioid-dependent patients. - Vergara-Rodriguez, Pamela; Tozzi, Mary Jo; Botsko, Michael; Nandi, Vijay; Altice, Frederick; Egan, James E; O'Connor, Patrick G; Sullivan, Lynn E; Fiellin, David A (Journal of acquired immune deficiency syndromes (1999), 2011)
The safety of buprenorphine/naloxone (bup/nx) in HIV-infected patients has not been established. Prior reports raise concern about hepatotoxicity and interactions with atazanavir.
Keywords: Anti-HIV Agents; Buprenorphine; Cohort Studies; Dose-Response Relationship, Drug; Drug Interactions; Drug-Induced Liver Injury; HIV Infections; Humans; Naloxone; Oligopeptides; Opioid-Related Disorders; Pyridines